PENGARUH GAYA KEPEMIMPINAN KHARISMATIK DAN PENGEMBANGAN KARIR TERHADAP PRODUKTIVITAS KARYAWAN PADA CV. GALAXI MITRA UTAMA BANDAR LAMPUNG - Nadya Ellyana Syndi (Jurnal Signaling, 2022)
The purpose of this study was to examine the effect of Leadership Style and Career Development on Employee Productivity. The use of these variables is based on the results of previous studies, namely: Balerang, Nainggolan, S.E., M.Sc (2017), Suyitno, Utomo (2017), Rachmatullah, M. R. (2017) and Saklit, I. W. (2017). This research was conducted at CV. Galaxi Mitra Utama Bandar Lampung, respondents used as many as 32 employees, The results showed the influence of leadership style and career development and significant impact on employee productivity. The influence of leadership style on employee productivity is significant and positive, the effect of career development on employee productivity is significant and positive.